A new look at the resolution of educational conflicts – Constructive processes through school mediation (Research, Society and Development, 2021)
The text aimed to study the school life, its violence, conflicts and mediation in the space and time of the school, using pedagogical and methodological tools that aim to exercise empathy, dialogue and conflict resolution, demonstrating how the Practices Restorative, through Mediation, can help to improve teaching and learning in the school universe. The methodology was developed through bibliographic reviews using a dialectical method in an ethnographic approach (Marconi; Lakatos, 2005), which sought theoretical support in authors such as: Abramoway (2002), Heredia (1999), Marshal (2019). The results showed that Restorative Practices, through the Mediation of Conflicts, Restorative Circles, Non-Violent Communication are tools that promote individuals to a new meaning and reconstruction in the way of teaching and learning inside and outside the school space.